2021
DOI: 10.3390/cancers13123064
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Interpretable Artificial Intelligence Model to Predict 10-Year Prostate Cancer Mortality

Abstract: Prostate cancer treatment strategies are guided by risk-stratification. This stratification can be difficult in some patients with known comorbidities. New models are needed to guide strategies and determine which patients are at risk of prostate cancer mortality. This article presents a gradient-boosting model to predict the risk of prostate cancer mortality within 10 years after a cancer diagnosis, and to provide an interpretable prediction. This work uses prospective data from the PLCO Cancer Screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The use of AI in predicting prostate cancer prognosis is also being actively studied. Bibault et al [ 17 ] used an AI algorithm to predict survival outcomes in prostate cancer patients. Using the prostate cancer dataset of 8,776 individuals from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, the training set included data from 7,021 individuals; the remaining 1,755 individuals made up the testing set.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of AI in predicting prostate cancer prognosis is also being actively studied. Bibault et al [ 17 ] used an AI algorithm to predict survival outcomes in prostate cancer patients. Using the prostate cancer dataset of 8,776 individuals from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, the training set included data from 7,021 individuals; the remaining 1,755 individuals made up the testing set.…”
Section: Resultsmentioning
confidence: 99%
“…Using the prostate cancer dataset of 8,776 individuals from the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, the training set included data from 7,021 individuals; the remaining 1,755 individuals made up the testing set. The accuracy of the 10-year survival rate and 10-year cancer-specific survival rate were 87% and 98%, respectively [ 17 ]. One study demonstrated the use of an AI model to predict the recurrence rate and progression of prostate cancer based on biomarkers [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One difference in our study with some previous work 5 , 6 is we do not include treatment methods, e.g., hormone therapy and radiotherapy, as input variables in our models. Our focus is to provide an initial risk estimation before recommending any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…But this gets more challenging with other methods that are not directly interpretable and are often considered as "black boxes", especially for the case of Neural Networks. For such cases, we thus used the SHapley Additive exPlanations (SHAP) as done in other machine learning implementations for health purpose predictions 33,34 . SHAP is based on the Shapley value, a game theoretic approach that calculates the average marginal contribution of a feature value across all possible coalitions.…”
Section: Model Interpretabilitymentioning
confidence: 99%